2005
DOI: 10.1080/03639040500216360
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cellulose Ether Polymers on Ibuprofen Release from Matrix Tablets

Abstract: Cellulose derivatives are the most frequently used polymers in formulations of pharmaceutical products for controlled drug delivery. The main aim of the present work was to evaluate the effect of different cellulose substitutions on the release rate of ibuprofen (IBP) from hydrophilic matrix tablets. Thus, the release mechanism of IBP with methylcellulose (MC25), hydroxypropylcellulose (HPC), and hydroxypropylmethylcellulose (HPMC K15M or K100M) was studied. In addition, the influence of the diluents lactose m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…Fickian diffusional release shows a rapid initial release, followed by a decrease in release owing to a chemical potential gradient (Bernard et al, 2004;Harris et al, 2006;Singh et al, 2012). These findings are in agreement with previous reports that have shown that poorly soluble drugs are released mainly by attrition mechanisms from hydrophilic and swellable polymeric matrices (Vueba et al, 2005). Table IV shows the values of r 2 and the rate constants obtained from the different kinetic models for the formulations investigated in this study.…”
Section: Resultssupporting
confidence: 82%
“…Fickian diffusional release shows a rapid initial release, followed by a decrease in release owing to a chemical potential gradient (Bernard et al, 2004;Harris et al, 2006;Singh et al, 2012). These findings are in agreement with previous reports that have shown that poorly soluble drugs are released mainly by attrition mechanisms from hydrophilic and swellable polymeric matrices (Vueba et al, 2005). Table IV shows the values of r 2 and the rate constants obtained from the different kinetic models for the formulations investigated in this study.…”
Section: Resultssupporting
confidence: 82%
“…This confirms that the drug:polymer ratio is an important factor affecting the drug release rates from HPMC matrices [64][65][66] . The gel layer that is formed delays further water uptake and the release of the dissolved drug.…”
Section: Drug Release Analysissupporting
confidence: 65%
“…Water insoluble filler excipients, such as DCP, tend to slow down drug release from HPMC matrices by getting entrapped within the matrix structure increasing the tortuosity of the matrix (32). Figure 6 shows the drug release from freshly prepared PVAc-PVP tablets prepared with different excipients.…”
Section: Drug Release and Modelingmentioning
confidence: 99%